Removal efficiency of lead, chromium and nickel by the cyanobacterium species: Synechoccocus elongates - Alshididi, Saba S. B.; Abed, Ibrahim J.; Al-Mashhadani, Mahmood K. H. (Iraqi Journal of Science, 2025)
This study investigates the impact of varying concentrations of Pb, Ni, and Cr heavy metal ions on the growth of Synechococcus elongatus (S. elongatus) and evaluates the effectiveness of S. elongatus in removing these heavy metal ions through biosorption, with a focus on identifying the residual ions that are not removed by this process. This study was conducted using five bioreactors filled with BG11 growth medium, each containing a different concentration of each heavy metal ion. The removal efficiency and the remaining ions of these heavy metals were determined by using an atomic absorption spectrophotometer by measuring the concentration of heavy metal ions in the initial solution and then every two days up to the end of the experiment. Maximum removal was achieved fourteen days of incubation with exposure to heavy metals at the concentrations of 0.5 ppm and 1.0 ppm (99.93% and 99.69% for Pb, 99.68% and 99.49% for Ni and 94.35% and 92.85% for Cr). At the concentration of 2.0 ppm, 70% absorption for Pb and Ni, 54.82% absorption for Cr occurred after fourteen days of incubation. At the concentrations 5.0 ppm and 10.0 ppm, microalgal growth troubled; this means that the medium was toxic.